Beach-spawning fishes : reproduction in an endangered ecosystem. - Martin, Karen L. M. (CRC Press/Taylor and Francis, 2014)
Beach-spawning fishes from exotic locations on most continents of the world provide spectacular examples of extreme adaptations during the most vulnerable life cycle stages. The beauty, intriguing biology, and importance of these charismatic fishes at the interface of marine and terrestrial ecosystems have inspired numerous scientific studies. Adaptations of behavior, physiology, development, and ecology are gathered together for the first time in this book.
Keywords: Fishes -- Spawning.; Fishes -- Reproduction.; Fishes -- Conservation -- Environmental aspects.; elektronické knihy; electronic books